Genetic epidemiology of psoriasis and psoriatic arthritis. (11th February 2005) - Rahman, P; Elder, J T
Abstract : Psoriasis and psoriatic arthritis (PsA) are interrelated disorders, as most patients with PsA also have psoriasis. Thus it is not surprising that epidemiological and immunogenetic studies have uncovered important links between these two disorders. Both disorders are highly heritable, and the prevalence of psoriasis is 19 times higher among first degree relatives of probands with PsA compared with the general population. Multiple human leucocyte antigen (HLA) associations are shared between psoriasis and PsA, though the magnitudes of these associations differ between the diseases. Genome-wide linkage studies have noted overlapping regions of significance for these two disorders within and outside the major histocompatibility complex (MHC) region. Thus, exploration of the genetic basis of psoriasis will likely strengthen the contention of an underlying genetic susceptibility for PsA and vice versa.